LAW ENFORCEMENT IN INDONESIA IN THE PERSPECTIVE OF LAW STATES - Husni Thamrin (Awang Long Law Review, 2020)
The existence of Indonesia as a state of law has given birth to regulations that cover all aspects of life which aimed to protecting human rights and law enforcement. In carrying out these objectives, the state must first be able to achieve and realize the law goals, such as the value of justice, certainty and usefulness. The most strenuous work at the moment is facing various polemics and law issues so that it has not been going well, of course, assertiveness is needed to uphold the commitment of law enforcement so as to realize a value of certainty and benefit for the people of Indonesia.